Implementation of Learning Media in the Introduction of Car Engine Components in Al Ashor Vocational School Students - Ridwan ridwan; Rafi Sangkar; Riyan Saputra (Journal of Transdisiplinary Studies in Education, 2026)
Background: Conventional learning methods used to introduce automobile engine components in vocational schools often limit students' ability to visualize component structures and functions effectively. Integrating Augmented Reality (AR) into learning offers an interactive approach that can enhance students' conceptual understanding. Aims: This study aimed to develop and implement an Augmented Reality (AR)-based learning medium to facilitate students' understanding of automobile engine components in vocational education. Methods: This study employed a Research and Development (R&D) approach using the ADDIE model, consisting of the analysis, design, development, implementation, and evaluation stages. The application was developed using Unity 3D, Blender, and the Vuforia SDK. Product feasibility was evaluated through black-box testing, media and material expert validation, and student response questionnaires. Results: Functional testing confirmed that all application features operated as intended. The media expert evaluation obtained an average score of 3.95, while the material expert assessment achieved 3.70, both indicating a highly feasible learning medium. Student responses reached 75.5%, reflecting positive perceptions of the application's usability, visual attractiveness, and contribution to understanding automobile engine components. Conclusion: The developed AR-based learning medium is considered feasible for vocational education and provides an interactive learning alternative that supports students in understanding automobile engine components more effectively.